Aplikasi Kaca pada Perancangan Desain Interior dan Arsitektur - Hartanti, Grace; Setiawan, Budi (Humaniora, 2014)
Glass is a clear and see-through material that comes from SiO2, which is a form of sands heated to 2000oC until they are melted. Glass has its own characteristics, such as: hard, transparent, clear, and fragile. The use of glass can be applied in a wide range of building elements, for example: roofing, walling, flooring, window and door, even staircase elements. By this wide range of utilities, this material could be very useful in design process. It can provide a wider view for small room with a lot of partitions or wall. It is because this material allows the light passing trough the material. That’s why people are able to see what’s behind the glass and eyes can see-through although the glass wall is limited by the glass. Hopefully, the research about diversity of glasses will be useful for designer, architect, and community in interior design and architecture world.